2003
DOI: 10.1110/ps.0306603
|View full text |Cite
|
Sign up to set email alerts
|

Library analysis of SCHEMA‐guided protein recombination

Abstract: The computational algorithm SCHEMA was developed to estimate the disruption caused when amino acid residues that interact in the three-dimensional structure of a protein are inherited from different parents upon recombination. To evaluate how well SCHEMA predicts disruption, we have shuffled the distantly-related ␤-lactamases PSE-4 and TEM-1 at 13 sites to create a library of 2 14 (16,384) chimeras and examined which ones retain lactamase function. Sequencing the genes from ampicillin-selected clones revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
142
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 141 publications
(143 citation statements)
references
References 26 publications
1
142
0
Order By: Relevance
“…Sequencing of the remaining clones revealed an additional eight sequences for a total of 31 unique functional chimeras (see Table 1, which is published as supporting information on the PNAS web site). Although no point mutations were found in the newly characterized chimeras, one of those previously identified as functional has two adjacent amino acid substitutions (28). Sequencing of unselected chimeras showed that nine of 13 (69%) contained frameshifts introduced during oligonucleotide synthesis.…”
Section: Methodsmentioning
confidence: 85%
See 4 more Smart Citations
“…Sequencing of the remaining clones revealed an additional eight sequences for a total of 31 unique functional chimeras (see Table 1, which is published as supporting information on the PNAS web site). Although no point mutations were found in the newly characterized chimeras, one of those previously identified as functional has two adjacent amino acid substitutions (28). Sequencing of unselected chimeras showed that nine of 13 (69%) contained frameshifts introduced during oligonucleotide synthesis.…”
Section: Methodsmentioning
confidence: 85%
“…In a previous study, we recombined PSE-4 and TEM-1 to create a well defined library of chimeras (28) and selected for those that allowed E. coli XL1-Blue to grow on 20 g͞ml ampicillin. Approximately 100 colonies were observed, and sequencing fifty of these clones identified 23 unique functional chimeras.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations